Apoptotic Effects of Xanthium strumarium via PI3K/AKT/mTOR Pathway in Hepatocellular Carcinoma. (7th November 2019) - Kim, Juyoung; Jung, Kyung Hee; Ryu, Hyung Won; Kim, Doo-Young; Oh, Sei-Ryang; Hong, Soon-Sun
Abstract : Xanthium strumarium (XS) has been traditionally used as a medicinal herb for treating inflammatory diseases, such as appendicitis, chronic bronchitis, rheumatism, and rhinitis. In this study, we yielded ethanol extracts from XS and investigated whether they could inhibit the progression of hepatocellular carcinoma (HCC) and its underlying mechanism. The XS-5 and XS-6 extracts dose-dependently inhibited the growth and proliferation in HCC cell lines. The apoptotic effects of them were observed via increased levels of cleaved caspase-3 and cleaved PARP, as well as elevated numbers of terminal deoxynucleotidyl transferase-mediated dUTP-biotin end labeling- (TUNEL-) positive apoptotic cells. They also decreased XIAP and Mcl-1 expression via loss of mitochondrial membrane potential. Additionally, they inhibited the invasion and migration of HCC cells. In an ex vivo model, the extracts significantly inhibited tumor cell growth and induced apoptosis by increasing the expression of the cleaved caspase-3. A mechanistic study revealed that they effectively suppressed PI3K/AKT/mTOR signaling pathways in HCC cells. Taken together, our findings demonstrate that they could efficiently not only induce apoptosis but also inhibit cell growth, migration, and invasion of human HCC cells by blocking the PI3K/AKT/mTOR pathway. We suggest XS-5 and XS-6 as novel natural anti-HCC agents.